Circulating Preproinsulin Signal Peptide–Specific CD8 T Cells Restricted by the Susceptibility Molecule HLA-A24 Are Expanded at Onset of Type 1 Diabetes and Kill β-Cells - Kronenberg, Deborah; Knight, Robin R.; Estorninho, Megan; Ellis, Richard J.; Kester, Michel G.; de Ru, Arnoud; Eichmann, Martin; Huang, Guo C.; Powrie, Jake; Dayan, Colin M.; Skowera, Ania; van Veelen, Peter A.; et al. (Diabetes (New York, N.Y.), 2012)
Type 1 diabetes results from T cell-mediated β-cell destruction. The HLA-A*24 class I gene confers significant risk of disease and early onset. We tested the hypothesis that HLA-A24 molecules on islet cells present preproinsulin (PPI) peptide epitopes to CD8 cytotoxic T cells (CTLs). Surrogate β-cell lines secreting proinsulin and expressing HLA-A24 were generated and their peptide ligandome examined by mass spectrometry to discover naturally processed and HLA-A24-presented PPI epitopes. A novel PPI epitope was identified and used to generate HLA-A24 tetramers and examine the frequency of PPI-specific T cells in new-onset HLA-A*24(+) patients and control subjects. We identified a novel naturally processed and HLA-A24-presented PPI signal peptide epitope (PPI(3-11); LWMRLLPLL). HLA-A24 tetramer analysis reveals a significant expansion of PPI(3-11)-specific CD8 T cells in the blood of HLA-A*24(+) recent-onset patients compared with HLA-matched control subjects. Moreover, a patient-derived PPI(3-11)-specific CD8 T-cell clone shows a proinflammatory phenotype and kills surrogate β-cells and human HLA-A*24(+) islet cells in vitro. These results indicate that the type 1 diabetes susceptibility molecule HLA-A24 presents a naturally processed PPI signal peptide epitope. PPI-specific, HLA-A24-restricted CD8 T cells are expanded in patients with recent-onset disease. Human islet cells process and present PPI(3-11), rendering themselves targets for CTL-mediated killing.